Tax Evasion and the Source of Income - Klarita Gërxhani; Arthur Schram (Tinbergen Institute, 2002)
A series of experiments in Albania and the Netherlands give us the opportunity to compare behavioral patterns related to tax evasion. Subjects have to decide between a random 'registered' income, the realization of which will be known to the experimenter for sure, and a random 'unregistered' income that will only be known to the experimenter with some (audit) probability. After the actual income has been determined, subjects have to report it and pay taxes accordingly. If they are audited, there is a fine for underreporting. This experiment was organized (separately) among high school pupils, high school teachers, university students, university teachers and university (non-academic) staff, in Albania and the Netherlands. The results show that (i) when tax evasion is possible, subject choose unregistered income more frequently; (ii) many subjects are willing to choose an income that allows for tax evasion but report their income honestly anyway; (iii) compliance increases with the audit probability; (iv) individual decisions to choose a type of income (registered vs. unregistered) and to evade taxes are made simultaneously; (v) Albanians evade taxes less than the Dutch do; (vi) pupils and students evade taxes more than teachers and personnel do; (vii) the differences across groups within a country are at least as large as the differences between the two countries. Finally, we argue that the distinct levels of tax evasion outside of the laboratory in the two countries are not attributable to different tax attitudes or cultures, but to different tax institutions and the way individuals have learned to deal with them.
Keywords: C91; H26; O17; O57; 330; Tax evasion; Cross-country studies; Experiments.; Steuervermeidung; Test; Niederlande; Albanien